Soft Computing Based Optimization and Decision Models To Commemorate the 65th Birthday of Professor José Luis "Curro" Verdegay - Pelta, David A.; Cruz Corona, Carlos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book offers a timely snapshot of current soft-computing research and solutions to decision-making and optimization problems, which are ubiquitous in the current social and technological context, addressing fields including logistics, transportation and data analysis.  Written by leading international experts from the United States, Brazil and Cuba, as well as the United Kingdom, France, Finland and Spain, it discusses theoretical developments in and practical applications of soft computing in fields where these methods are crucial to obtaining better models, including: intelligent transportation systems, maritime logistics, portfolio selection, decision- making, fuzzy cognitive maps, and fault detection.  The book is dedicated to Professor José L. Verdegay, a pioneer who has been actively pursuing research in fuzzy sets theory and soft computing since 1982, in honor of his 65th birthday.
A Review of Soft Computing Techniques in Maritime Logistics and its Related Fields -- Intelligent Data Analysis, Soft Computing and Imperfect Data -- Soft Computing Methods in Transport and Logistics -- Applications of Soft Computing in Intelligent Transportation Systems -- Fuzzy Cognitive Maps based Models for Pattern Classification: Advances and Challenges -- A proposal of on-line detection of new faults and automatic learning in fault diagnosis -- Fuzzy Portfolio Selection Models for dealing with Investor's Preferences -- Gradual numbers and fuzzy solutions to fuzzy optimization problems -- A modal account of preference in a fuzzy setting -- The single parameter family of Gini Bonferroni welfare functions and the binomial decomposition, transfer sensitivity and positional transfer sensitivity.
Keywords: Computational intelligence; Mathematical optimization; Calculus of variations; Artificial intelligence; Operations research; Computational Intelligence; Calculus of Variations and Optimization; Artificial Intelligence; Operations Research and Decision Theory